2020
DOI: 10.1103/physrevb.101.064508
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and superconducting anisotropy in Ni-doped RbEuFe4As4 single crystals

Abstract: We investigate the effect of Ni doping on the Fe-site in single crystals of the magnetic superconductor RbEuFe4As4 for doping concentrations of up to 4%. A clear suppression in the superconducting transition temperature is observed in specific heat, resistivity and magnetization measurements. Upon Ni-doping, the resistivity curves shift up in a parallel fashion indicating a strong increase of the residual resistivity due to scattering by charged dopand atoms while the shape of the curve and thus the electronic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Muon spin rotation (µSR) measurements of polycrystaline samples [22] indicated that under hydrostatic pressure the superconducting transition temperature T c decreased, while the magnetic transition temperature T m increased, suggesting no coupling between s ± superconductivity typical for IBSC and exotic magnetic order of Eu. A recent study of the magnetism and superconductivity in Ni-doped RbEuFe 4 As 4 showed that upon doping the SC transition critical temperature T c decreased, but the Eu magnetic transition temperature T m is hardly affected [23]. This suggests that Eu magnetism and superconductivity might be weakly dependent from each other.…”
Section: Introductionmentioning
confidence: 98%
“…Muon spin rotation (µSR) measurements of polycrystaline samples [22] indicated that under hydrostatic pressure the superconducting transition temperature T c decreased, while the magnetic transition temperature T m increased, suggesting no coupling between s ± superconductivity typical for IBSC and exotic magnetic order of Eu. A recent study of the magnetism and superconductivity in Ni-doped RbEuFe 4 As 4 showed that upon doping the SC transition critical temperature T c decreased, but the Eu magnetic transition temperature T m is hardly affected [23]. This suggests that Eu magnetism and superconductivity might be weakly dependent from each other.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, according to the prediction by Anderson and Suhl, the periodicity of the spin helix d is correlated with the supercondcuting coherence length ξ 0 in the form of d ∝ (ξ 0 ) 1/3 . 42 As the superconducting transition temperature T SC and the upper critical field H c2 decrease with increasing Ni doping, 23 ξ 0 increases according to the Ginzburg-Landau formalism H c2 = Φ 0 /2πξ 0 2 , which is consistent with the diminishing θ and increasing helix periodicity d . Although some recent spectroscopic measurements seem to suggest the decoupling of magnetism from Eu from superconducting FeAs layers, 43,44 we note that a recent scanning Hall microscopy experiment has revealed a pronounced suppression of the superfluid density near the Eu magnetic ordering temperature in Eu1144, indicating a pronounced exchange interaction between the superconducting and magnetic subsystems.…”
Section: Discussionmentioning
confidence: 54%
“…Γ 1 allows the c-axis aligned ferromagnetic Eu layers stacking with modulated moment size values at different layers, which is not consistent with the easy-plane magnetization as revealed from the single-crystal sample with a similar Ni doping level. 23 On Bragg reflections from the RbEu(Fe0.91Ni0.09)4As4 main phase, EuFe2As2 impurity, RbFe2As2 impurity, vanadium sample container, as well as the magnetic Bragg reflections from the RbEu(Fe0.91Ni0.09)4As4 main phase and the EuFe2As2 impurity, respectively. (e), (f) and (g) show the enlarged high-resolution diffraction patterns at 2 and 20 K around the (0 0 1), (0 0 2) and (0 0 3) nuclear peak positions, respectively, illustrating the commensurate magnetic contributions with k = 0 at 2 K. the other hand, Γ 5 allows the in-plane aligned ferromagnetic Eu layers to stack helically along the c axis, with a constant moment size value at different layers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations